Risk Analysis of Hot Working in Confined Space Using Confined Space Risk Analysis (CRSA) and Bowtie Analysis Method on LPG Tanker Repair Process - Dhanistha, Wimala L; Silvianita, Silvianita; M, Roshi (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2023)
Confined space is a room that is large enough and has a configuration in such a way that workers can enter and do work in it. In the ship repair process it is not uncommon to do it in a confined space area. . The purpose of writing this final project is to identify hazards and carry out risk assessments in hot working in confined spaces in the LPG tanker ship repair process so that the dominant hazard is obtained, the causes and consequences of the dominant hazard are identified, and the right dominant risk control can be identified. This study begins with the identification of the characteristics of confined space on ships by grouping them into 7 risk categories of confined space. Then carry out risk identification by explaining the components of a risk, including: types of hazards, dangerous work, dangerous events and the consequences that can occur. After that, an initial risk assessment was carried out for hot working in confined spaces on ship repairs presented in matrix form. After that, risk control is carried out and the final risk reassessment for hot working in confined space on ship repair is carried out by continuing the matrix that was previously made. In the final stage, an analysis is carried out using the bowtie method to analyze the causes, impacts, and controls of these risks.